Barriers to Health Care in Rural Mozambique: A Rapid Ethnographic Assessment of Planned Mobile Health Clinics for ART - Amee Schwitters; P Lederer; Leah Zilversmit; Paula Samo Gudo; Isaías Ramiro; Luisa Cumba; Epifanio Mahagaja; Kebba Jobarteh (2015)
ABSTRACT Background: In Mozambique, 1.6 million people are living with HIV, and over 60% of the population lives in rural areas lacking access to health services. Mobile health clinics, implemented in 2013 in 2 provinces, are beginning to offer antiretroviral therapy (ART) and basic primary care services. Prior to introduction of the mobile health clinics in the communities, we performed a rapid ethnographic assessment to understand barriers to accessing HIV care and treatment services and acceptability and potential use of the mobile health clinics as an alternative means of service delivery. Methods: We conducted assessments in Gaza province in January 2013 and in Zambezia Province in April–May 2013 in districts where mobile health clinic implementation was planned. Community leaders served as key informants, and chain-referral sampling was used to recruit participants. Interviews were conducted with community leaders, health care providers, traditional healers, national health system patients, and traditional healer patients. Interviewees were asked about barriers to health services and about mobile health clinic acceptance. Results: In-depth interviews were conducted with 117 participants (Gaza province, n = 57; Zambezia Province, n = 60). Barriers to accessing health services included transportation and distance-related issues (reliability, cost, and travel time). Participants reported concurrent use of traditional and national health systems. The decision to use a particular health system depended on illness type, service distance, and lack of confidence in the national health system. Overall, participants were receptive to using mobile health clinics for their health care and ability to increase access to ART. Hesitations concerning mobile health clinics included potentially long wait times due to high patient loads. Participants emphasized the importance of regular and published visit schedules and inclusion of community members in planning mobile health clinic services. Conclusion: Mobile health clinics can address many barriers to uptake of HIV services, particularly related to transportation issues. Involvement of community leaders, providers, traditional healers, and patients, as well as regularly scheduled mobile clinic visits, are critical to successful service delivery implementation in rural areas.